Production method for anodizing and chambering corrosion electrode foil

Through a multi-step production method, including pretreatment, pore corrosion, pore reaming corrosion, sol-gel coating and anodization treatment, the problem of poor quality of anodized pore reaming corrosion electrode foil in the prior art is solved, and high specific capacity, uniformity and high performance electrode foil production is achieved.

CN119560312APending Publication Date: 2025-03-04ANHUI YAMING ALUMINUM TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411649420.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The prior art is difficult to effectively produce high-quality anodized into pore-rejuvenating corroded electrode foil, resulting in uneven corrosion and inconsistent hole size during the decomposition process, affecting the performance of the electrode foil.

Method used

A multi-step production method is employed, including pretreatment, pore corrosion, reaming corrosion, sol-gel coating and anodization treatment. The specific steps include treating the aluminum foil in a sodium hydroxide solution, then performing ultrasonic treatment in a mixed solution of hydrochloric acid and sulfuric acid to generate pore corrosion, then amplifying the pores in the phosphoric acid solution, and anodizing the chemical solution.

Benefits of technology

Through this production method, the specific capacitance and performance of the aluminum foil can be significantly improved, and the uniformity and high quality of the electrode foil can be ensured. Specifically, the specific capacitance of the foil reaches 0.84μF/cm2 (375Vf), and meets the requirements of high strength, multiple bending and low residual chloride.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a production method for anodizing, chambering and corroding an electrode foil, belongs to the technical field of electrode foils, and adopts ultrasonic waves to generate a cavitation effect in liquid, promote a corrosion process and improve uniform hole forming and performance of an aluminum foil. A domestic plain aluminum foil of 132 microns is used, and proper holes are obtained through three-stage treatment of alkali washing, hole-forming corrosion and chambering corrosion and hole-forming corrosion of a mixed solution composed of sulfuric acid and hydrochloric acid. The polyethyleneimine is added into a reaming phosphoric acid solution to slow down corrosion, aluminum foil holes subjected to three-stage treatment contain Cl <->, metal impurities, phosphoric acid and the like, corrosion is caused to products, and the quality of oxidation films is reduced. Impurities are cleaned through dilute nitric acid, a compact and firm oxidation film is obtained, then sol-gel coating and subsequent formation treatment are carried out, the anode formation chambering corrosion electrode foil is obtained, and the specific capacitance of the foil is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrode foils, and in particular relates to a production method of an anodized hole-expanding corrosion electrode foil. Background Art

[0002] Electronic aluminum foil is an energy storage material among functional materials. It is a product of a special high-purity aluminum foil that is subjected to anodic corrosion expansion and anodic formation to form a dielectric oxide film on the surface. It is a key raw material for manufacturing aluminum electrolytic capacitors. In the electrolytic capacitor family, aluminum electrolytic capacitors are widely used in the communication market, automotive electronics, household appliances, industrial fields, military and aerospace fields due to their superior performance and low price. In the past 20 years, it has been greatly developed worldwide, maintaining a position of more than one-third of the entire capacitor market, and the annual growth rate has remained stable at 4% to 6%. As the core material of aluminum electrolytic capacitors, the performance and quality, shape and size of the capacitor depend to a large extent on the chemical foil used, and the performance of the chemical foil is mainly determined by the corrosion foil. Those skilled in the art are in urgent need of developing a production method for anodized expansion corrosion electrode foil to meet existing usage requirements and market demand. Summary of the invention

[0003] The purpose of the present invention is to provide a production method of anodized hole-expanding corrosion electrode foil to solve the above technical problems.

[0004] A method for producing an anodized hole-expanding corrosion electrode foil comprises the following steps: (1) Pretreatment: The aluminum foil is treated in a sodium hydroxide solution with a molar concentration of 0.80 mol / L to 1.0 mol / L at 60°C for 30 to 40 seconds, and then dried in an air environment at room temperature; (2) Pitting corrosion: The pre-treated aluminum foil was placed in a mixed solution containing 1 mol / L to 1.5 mol / L hydrochloric acid and 1 mol / L to 1.5 mol / L hydrochloric acid in a volume ratio of 1:1 at a temperature of 60°C to 70°C, and ultrasonically treated at a current density of 150 mA / cm 2 ~300mA / cm 2 The DC current and the pore corrosion time are 100s to 120s; The presence of metal impurities in the mixed solution will significantly affect the corrosion potential during the corrosion process, resulting in obvious and uneven corrosion holes or holes of different sizes, affecting the quality of the corrosion foil.

[0005] (3) Hole expansion corrosion: Then the hole is expanded in a phosphoric acid solution with a molar concentration of 0.6 mol / L to 1.0 mol / L, and the applied hole expansion current is 0.1 A / cm 2 ~0.15A / cm 2The hole expansion time is 30s to 60s, and the aluminum foil after hole expansion and corrosion is cleaned with nitric acid solution; (4) Sol-gel coating: Titanium dioxide sol is evenly coated on the surface of the aluminum foil after hole expansion and corrosion. The titanium dioxide sol coated on the surface of the aluminum foil after hole expansion and corrosion per unit area is 1.5 mg / cm 2 ~2mg / cm 2 , and dried at ambient temperature, then dried in an oven at 100°C for 10 min, transferred to a muffle furnace at 450-550°C for calcination for 10-15 min, and then cooled to room temperature at a rate of 5°C / min, then blown off the surface ash and washed with anhydrous ethanol, and dried at 60°C to obtain a sol-gel coated aluminum foil; (5) Chemical formation: The aluminum foil coated with the sol-gel is then subjected to anodizing treatment. The anodizing process is carried out in a two-electrode system, with the aluminum foil coated with the sol-gel as the anode and the platinum sheet as the cathode. Ammonium pentaborate having a mass fraction of 0.09% to 0.1% is added to a boric acid aqueous solution having a mass concentration of 10% to form a chemical forming solution. The chemical forming temperature is 85°C to 90°C, and the chemical forming current density is 30 mA / cm 2 ~40mA / cm 2 The forming voltage is 250V~300V, and the constant current and constant voltage forming is 6min~10min to obtain the anodic forming hole expansion corrosion electrode foil.

[0006] Furthermore, the aluminum foil described in step (1) is a soft aluminum foil having an aluminum content of ≥99.99%, a cubic texture occupancy of ≥95%, and a thickness of 120 μm to 132 μm.

[0007] Furthermore, in step (3), the aluminum foil that has undergone pore corrosion is washed with pure water, placed in a phosphoric acid solution at a temperature of 60° C. to 70° C., and 0.3% to 0.4% by weight of polyethyleneimine is added thereto.

[0008] Furthermore, the titanium dioxide sol is an anatase sol with water as the dispersion medium, an average particle size of 10 nm, a pH of 3, and a titanium dioxide content of 10%.

[0009] Furthermore, the ultrasonic frequency is 20kHz to 25kHz, and the ultrasonic power is 500W to 600W.

[0010] The present invention has the following beneficial effects: The present invention utilizes the cavitation effect generated by ultrasound in liquid to promote the corrosion process, promote mass transfer on the surface of aluminum foil and inside the tunnel hole, circulation of solution, and electrochemical reaction, thereby facilitating uniform pore formation in aluminum foil, increasing tunnel hole density, tunnel hole length and length consistency, thereby improving the specific volume and performance of aluminum foil. 132μm domestic aluminum foil is used as raw material. The foil raw material used has suitable hole thickness and stable quality, and the cubic texture (100) crystal plane occupancy rate is greater than 95%. Alkaline washing, pore formation corrosion, and hole expansion corrosion are used in three stages. A mixed solution composed of sulfuric acid and hydrochloric acid is used for pore formation corrosion to obtain uniform initial holes of appropriate size. Polyethyleneimine is added to the hole expansion phosphoric acid solution to slow down the corrosion rate and improve the hole expansion effect. The aluminum foil holes after the three-stage treatment contain Cl - , metal impurities, phosphoric acid and other impurities will cause various defects such as continued corrosion, failure to increase voltage or damage to the quality of the aluminum oxide film during the chemical process. The cleaning liquid dilute nitric acid cleans all kinds of impurities, making the surface oxide film denser and stronger, and then through sol-gel coating, after subsequent chemical treatment, the anodic expansion corrosion electrode foil is obtained, which effectively improves the specific capacitance of the foil, and the specific capacitance of the corrosion foil reaches 0.84μF / cm 2 (375V f ). DETAILED DESCRIPTION

[0011] The present invention is described below with specific examples, but is not intended to be limiting of the present invention. Example 1

[0012] Raw materials and equipment: Shangqiu Keyuan aluminum foil, purity of 99.99%, thickness of 132μm, cubic texture occupancy greater than 95%. Zhongde Electronic Materials Industrial Grade EL Hydrochloric Acid, Runma Electronic Materials Industrial Grade LP Sulfuric Acid, Chengxing Phosphorus Chemical and Electrical Industry 85% Phosphoric Acid. Titanium dioxide sol is an anastacia sol Anhui Jingrui VK-TA33 with water as the dispersion medium, average particle size of 10nm, pH3, and titanium dioxide content of 10%. Yaming Aluminum fully automatic etching machine; high and low voltage distribution cabinets; ultrapure water treatment equipment (100m 3 / h, EDI, 18MΩ) produced ultrapure water. Polyethyleneimine QL-A1000-B1. Anqing Jingxiang New Materials Capacitor Grade Ammonium Pentaborate. Peixian Dongfang Electronic Materials Factory Capacitor Grade Boric Acid.

[0013] The production method of anodizing and corroding electrode foil comprises the following steps: (1) Pretreatment: The aluminum foil was treated in a 0.8 mol / L sodium hydroxide solution at 60°C for 30 seconds and then dried in an air environment at room temperature. (2) Pitting corrosion: The pretreated aluminum foil was placed in a mixed solution of 1 mol / L hydrochloric acid and 1 mol / L sodium hydroxide solution at a volume ratio of 1:1 at 60°C and ultrasonically treated at a current density of 150 mA / cm2 The direct current was 100 s for the pore etching time, the ultrasonic frequency was 20 kHz, and the ultrasonic power was 500 W; (3) pore enlargement corrosion: the pores were then enlarged in a phosphoric acid solution with a molar concentration of 0.6 mol / L. The aluminum foil after pore enlargement was washed with pure water and placed in a phosphoric acid solution with a temperature of 60 °C, and 0.3% by mass of polyethyleneimine was added. The pore enlargement current was 0.A / cm 2 , the hole expansion time is 30s, and the aluminum foil after hole expansion corrosion is cleaned with nitric acid solution; (4) Sol-gel coating: titanium dioxide sol is evenly coated on the surface of the aluminum foil after hole expansion corrosion, and the titanium dioxide sol coated on the surface of the aluminum foil after hole expansion corrosion per unit area is 1.5mg / cm 2 , and dried at ambient temperature, then dried in an oven at 100°C for 10 min, transferred to a muffle furnace for calcination at 450°C for 10 min, and then cooled to room temperature at a rate of 5°C / min, then blown off the surface ash and washed with anhydrous ethanol, and dried at 60°C to obtain a sol-gel coated aluminum foil; (5) Chemical formation: The sol-gel coated aluminum foil is then anodized. The anodization process is carried out in a two-electrode system, with the sol-gel coated aluminum foil as the anode and the platinum sheet as the cathode. Ammonium pentaborate with a mass fraction of 0.09% is added to a boric acid aqueous solution with a mass concentration of 10% to form a chemical solution (resistivity 1550Ω·cm at 70°C, pH 3.5 at 50°C), the chemical temperature is 85°C, and the chemical current density is 30mA / cm 2 The formation voltage is 250V, and the constant current and constant voltage formation is 6 minutes to obtain the anodic expansion corrosion electrode foil.

[0014] Product performance: The foil has a clean and uniform appearance, with no pinholes, spots, color changes, powder, stripes, wrinkles, etc. on the surface. Width 500mm. Tensile strength> 20N / ㎝, bending strength of 1mm chuck curvature radius ≥ 70 times, bending strength of 3.5mm chuck curvature radius ≥ 120 times, residual chloride 1.0mg / m 2 Below, 0.84μF / cm 2 (375V f ). Example 2

[0015] Raw materials: Shangqiu Keyuan aluminum foil, purity of 99.99%, thickness of 120μm, cubic texture occupancy greater than 95%. Jingjiu Microelectronics Materials Industrial Grade EL Hydrochloric Acid, Jingjiu Microelectronics Materials Industrial Grade LP Sulfuric Acid, Zhongde Electronic Materials Industrial Grade CMOS Phosphoric Acid. Titanium dioxide sol is an anastase sol Anhui Jingrui VK-TA33 with water as the dispersion medium, average particle size of 10nm, pH3, and titanium dioxide content of 10%. Yaming Aluminum Industry fully automatic etching machine; high and low voltage distribution cabinets; ultrapure water treatment equipment (100m3 / h, EDI, 18MΩ) produced ultrapure water. Polyethyleneimine QL-A1000-B1. Anqing Jingxiang New Materials Capacitor Grade Ammonium Pentaborate. Baili Chemical Capacitor Grade Boric Acid.

[0016] The production method of anodizing and corroding electrode foil comprises the following steps: (1) Pretreatment: The aluminum foil was treated in a 1.0 mol / L sodium hydroxide solution at 60°C for 40 seconds and then dried in an air environment at room temperature. (2) Pitting corrosion: The pretreated aluminum foil was placed in a mixed solution of 1.5 mol / L hydrochloric acid and 1.5 mol / L sodium hydroxide at a volume ratio of 1:1 at 70°C and ultrasonically treated at a current density of 300 mA / cm 2 The direct current was 1000 W, the pore etching time was 120 s, the ultrasonic frequency was 25 kHz, and the ultrasonic power was 600 W; (3) pore expansion corrosion: the pores were then expanded in a phosphoric acid solution with a molar concentration of 1.0 mol / L. The aluminum foil after pore expansion was washed with pure water and placed in a phosphoric acid solution at a temperature of 70 ° C, and 0.4% by mass of polyethyleneimine was added. The pore expansion current was 0.15 A / cm 2 , the hole expansion time is 60s, and the aluminum foil after hole expansion corrosion is washed with nitric acid solution; (4) Sol-gel coating: titanium dioxide sol is evenly coated on the surface of the aluminum foil after hole expansion corrosion, and the titanium dioxide sol coated on the surface of the aluminum foil after hole expansion corrosion per unit area is 2mg / cm 2 , and dried at ambient temperature, then dried in an oven at 100°C for 10 min, transferred to a muffle furnace for calcination at 550°C for 15 min, and then cooled to room temperature at a rate of 5°C / min, then blown off the surface ash and washed with anhydrous ethanol, and dried at 60°C to obtain a sol-gel coated aluminum foil; (5) Chemical formation: The sol-gel coated aluminum foil is then anodized. The anodization process is carried out in a two-electrode system, with the sol-gel coated aluminum foil as the anode and the platinum sheet as the cathode. Ammonium pentaborate with a mass fraction of 0.1% is added to a boric acid aqueous solution with a mass concentration of 10% to form a chemical solution (resistivity 1650Ω·cm at 70°C, pH 3.7 at 50°C), the chemical temperature is 90°C, and the chemical current density is 40mA / cm 2 The forming voltage is 300 V, and the constant current and constant voltage forming is performed for 10 minutes to obtain the anodic forming hole expansion corrosion electrode foil.

[0017] Product performance: The foil has a clean and uniform appearance, with no pinholes, spots, color changes, powder, stripes, wrinkles, etc. on the surface. Width 500mm. Tensile strength> 20N / ㎝, bending strength of 1mm chuck curvature radius ≥ 70 times, bending strength of 3.5mm chuck curvature radius ≥ 120 times, residual chloride 1.0mg / m 2Below, 0.8μF / cm 2 (375Vf).

[0018] Note: Refer to SJ / T11140-2022 Electrode foil for aluminum electrolytic capacitors.

Claims

1. A method for producing an anodized hole-expanding corrosion electrode foil, characterized in that: The following steps are involved: (1) Pretreatment: Treat the aluminum foil in a sodium hydroxide solution with a molar concentration of 0.8 mol / L to 1.0 mol / L at 60°C for 30s to 40s, and then dry it in an air environment at room temperature; (2) Pitting corrosion: The pre-treated aluminum foil is placed in a mixed solution of 1 mol / L to 1.5 mol / L hydrochloric acid and 1 mol / L to 1.5 mol / L hydrochloric acid at a volume ratio of 1:1 at a temperature of 60°C to 70°C, and ultrasonically treated at a current density of 150 to 300 mA / cm 2 The DC current and the pore corrosion time are 100s to 120s; (3) Hole expansion corrosion: Then the hole is expanded in a phosphoric acid solution with a molar concentration of 0.6 mol / L to 1.0 mol / L, and the applied hole expansion current is 0.1 A / cm 2 ~0.15A / cm 2 The hole expansion time is 30s to 60s, and the aluminum foil after hole expansion and corrosion is cleaned with nitric acid solution; (4) Sol-gel coating: Titanium dioxide sol is evenly coated on the surface of the aluminum foil after hole expansion and corrosion. The titanium dioxide sol coated on the surface of the aluminum foil after hole expansion and corrosion per unit area is 1.5 mg / cm 2 ~2mg / cm 2 , and dried at ambient temperature, then dried in an oven at 100°C for 10 minutes, transferred to a muffle furnace at 450°C to 550°C for calcination for 10 to 15 minutes, and then cooled to room temperature at a rate of 5°C / min, then blown off the surface ash and washed with anhydrous ethanol, and dried at 60°C to obtain a sol-gel coated aluminum foil; (5) Chemical formation: The aluminum foil coated with the sol-gel is then subjected to anodizing treatment. The anodizing process is carried out in a two-electrode system, with the aluminum foil coated with the sol-gel as the anode and the platinum sheet as the cathode. Ammonium pentaborate having a mass fraction of 0.09% to 0.1% is added to a boric acid aqueous solution having a mass concentration of 10% to form a chemical forming solution. The chemical forming temperature is 85°C to 90°C, and the chemical forming current density is 30 mA / cm 2 ~40mA / cm 2 The forming voltage is 250V~300V, and the constant current and constant voltage forming is 6min~10min to obtain the anodic forming hole expansion corrosion electrode foil.

2. The method for producing an anodized hole-expanding corrosion electrode foil according to claim 1, characterized in that: The aluminum foil described in step (1) is a soft aluminum foil with an aluminum content of ≥99.99%, a cubic texture occupancy of ≥95%, and a thickness of 120 μm to 132 μm.

3. The method for producing an anodized hole-expanding corrosion electrode foil according to claim 1, characterized in that: In step (3), the aluminum foil that has been corroded by pores is washed with pure water, placed in a phosphoric acid solution at a temperature of 60° C. to 70° C., and 0.3% to 0.4% by weight of polyethyleneimine is added.

4. The production method according to claim 1, characterized in that The titanium dioxide sol is an anatase sol with water as a dispersion medium, an average particle size of 10 nm, a pH of 3, and a titanium dioxide content of 10%.

5. The method for producing an anodized hole-expanding corrosion electrode foil according to claim 1, characterized in that: The ultrasonic frequency is 20kHz to 25kHz, and the ultrasonic power is 500W to 600W.